Censored Translations in Franco’s Spain: The TRACE Project — Theatre and Fiction (English-Spanish) - Merino, Raquel; Rabadán, Rosa (TTR, 2002)
AbstractThis article explores whether translational phenomena that are particular to censoring societies, such as Franco’s Spain, exist and, if so, whether they are exclusive to this type of recipient context. By using data from the TRACE project, translated theatre and fiction are analysed in terms of both the external restrictions imposed by official censorship and the long-term effects of official censorship on the recipient context. The study reveals three outstanding transfer processes during the period–adaptation, pseudotranslation and the massive cloning of genres, settings and character stereotypes originally imported through translation–, as well as the prevalence of intersemiotic chains that linked texts across languages and textual mode boundaries. When compared with work done on present-day texts translated from English to Spanish, our findings seem to indicate that these phenomena were more widespread in the period under study but cannot be considered exclusive to official censorship contexts.